Polyploid giant cancer cells with budding and the expression of cyclin E, S-phase kinase-associated protein 2, stathmin associated with the grading and metastasis in serous ovarian tumor - Lv, Hongcheng (BioMed Central, 2014)
BACKGROUND: We previously reported that polyploid giant cancer cells (PGCCs) exhibit cancer stem cell properties and express cell cycle-related proteins. HEY PGCCs induced by cobalt chloride generated daughter cells and the daughter cells had a strong migratory and invasive ability. This study is to compare the expression of cyclin E, S-phase kinase-associated protein 2 (SKP2), and stathmin between PGCCs with budding and control HEY cells, and determine the clinicopathological significance of cell cycle-related protein expression in ovarian tumors. METHODS: We used western blot and immunocytochemical staining to compare the expression levels of cyclin E, SKP2 and stathmin between PGCC with budding daughter cells and control HEY cells. In addition, immunohistochemical staining for cyclin E, SKP2 and stathmin was performed on a total of 80 paraffin-embedded serous ovarian tumor tissue samples. The samples included 21 cases of primary high-grade carcinoma (group I) and their metastatic tumors (group II), 26 cases of primary low-grade carcinoma without metastasis (group III), and 12 cases of serous borderline cystadenoma (group IV). RESULTS: Single PGCC with budding in the stroma showed high correlation with the metastasis of ovarian carcinoma. Group I had a significantly higher number of single PGCCs with budding in the stroma than group III (85.71% [18/21] vs. 23.08% [6/26] cases; χ(2) = 18.240, P = 0.000). The expression of cyclin E, SKP2, and stathmin was compared among the four groups. The expression levels of cyclin E, SKP2, and stathmin increased with the malignant grade of ovarian tumors and group II had the highest expression levels. The expression of cyclin E (χ(2) = 17.985, P = 0.000), SKP2 (χ(2) = 12.384, P = 0.000), and stathmin (χ(2) = 20.226, P = 0.000) was significantly different among the 4 groups. CONCLUSIONS: These data suggest that the cell cycle-related proteins cyclin E, SKP2, and stathmin may be valuable biomarkers to evaluate the metastasis in patients with ovarian serous carcinoma. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/1471-2407-14-576) contains supplementary material, which is available to authorized users.